Acute kidney injury due to star fruit ingestion: A case report - Ananna, Mehruba Alam; Hasan, Rubayet; Samad, Tabassum; Rahim, Mohammad Abdur; Rahman, Mohammad Erfanur; Haque, Wasim Mohsinul; Billah, Mohammad; Hoque, Hasna Fahmima; Afroz, Farhana; Afroz, Samira Rabat; et al. (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Star fruit (Avarrhoa carambola) is a fruit from oxalidace family. lt is found in many countries of the world including Bangladesh. But its ingestion or drinking star fruit juice may lead to intoxication especially in patients with chronic kidney disease and manifestations might be neurological or nephrological. lt may also cause acute kidney injury in patients with previously normal renal function. Here we are presenting a case who presented with acute kidney injury after star fruit ingestion with previously unknown renal function impairment. The etiology was confirmed by histopathological examination after doing renal biopsy. This renal function impairment is mainly due to oxalate crystal induce nephropathy which is richly abundant in star fruit. His renal function was improved ·with conservative management. Physicians should be alert to consider the ingestion of star fruit as a cause of acute kidney injury in a patient even in the absence of previous renal function impairment.